The Use of Wattpad as a Bibliotherapy Medium in Islamic Counseling Services to Improve Adolescents’ Mental Health - Suwatah, Suwatah; Hotim, Hotim; Maylina, Putri Rachmanda (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2024)
The aim of this research is to find out how the Wattpad application is used as a bibliotherapy medium in Islamic counseling services to improve adolescent mental health. This research uses a literature study research method which can be processed by collecting information through previous research references and then compiling it to draw conclusions. The results of the research analysis obtained are that by utilizing the Wattpad application, counselors can implement bibliotherapy media in Islamic counseling services. The steps include identifying the client’s problem, determining a diagnosis (for example, low adolescent mental health), formulating a prognosis (reading therapy), and selecting an appropriate book from the Wattpad application. After providing reading material, the counselor carries out follow-up actions to monitor changes that occur in the counselee. So it can be concluded that the Wattpad application as an Islamic counseling bibliotherapy medium to improve adolescent mental health can be implemented.